TO STUDY THE AWARENESS AND ADOPTION OF PRODUCTION PRACTICES OF RICE GROWERS IN TALUKA SHAHDADKOT, SINDH, PAKISTAN - Abdul Rasool; Asif Ali; Izhar Ahmad; MARIFOVNA, Muhammad Anwar (European Journal of Life Safety and Stability (2660-9630), 2021)
Rice crop is deemed to be the stable food for more than half of the world’s population, playing the significant role for the economic importance in agriculture development, as well as poverty reduction. Keeping in view the concern of local people over awareness and adoption of production practices of rice growers, the researcher conducted a study in Taluka Shahdadkot, Sindh province of Pakistan. The quantified data from 160 respondents were collected on a valid and reliable extent using likert scale and analyzed through SPSS. The results revealed that majority of the respondents (M=37.7) years having the experience of almost (M=13.8) years of farming experience with roughly (54%) of primary education, showing somehow the maturity level of the respondents connected with rural areas. The results revealed that, majority of rice growers were maintaining extremely high level of knowledge regarding rice production practices such as irrigation practices, land management practices, soil test, transplanting, broadcasting and proper time of sowing with more than satisfactory level. While, there had some flaws noticed in adoption of new rice technology, where overwhelming (75%) of the farmers were disagree for exploiting the improved rice verities having mean M=-.019; SD=2.210) and were not ready to adopt the direct seeded rice. However, there was the discrepancy of modern technologies which could bring more production as compared to the traditional one, utilized by the developed nations. So far, diverse barriers were also noticed regarding improved verities, diffusion of technical knowledge, adopting new agricultural production activities and poor extension services. Thus, the research recommended that, the Government as well as Rice research institute and Agriculture extension services should take interest in growers for granting the awareness and adoption regarding new production practices such as direct rice seeded technology as well as advance variety production techniques. Besides that, training must be raised through technology diffusions and the mobilization to farmers by the public as well as private extension services for the sustainability.